BIMBINGAN DAN KONSELING DI SEKOLAH DASAR NEGERI CEPOKO 3 KECAMATAN NGRAMBE KABUPATEN NGAWI: GUIDANCE AND COUNSELING AT CEPOKO STATE ELEMENTARY SCHOOL 3 - Yudhiarti, Ndaru Putri (Jurnal Al-Ilmu: Jurnal Penelitian dan Pendidikan Madrasah Ibtidaiyah, 2022)
In realizing the goals of national education, it is necessary to integrate all components of education, one of which is the component of guidance and counseling. In order to realize the educational goals of the Cepoko 3 public elementary school, it also carries out a program of guidance and counseling services. Guidance and counseling service programs are implemented to assist and direct students in overcoming the problems they are facing. Problems faced by students related to academic or non-academic. The purpose of this study was to determine how the implementation of the guidance and counseling service program that had been implemented at SDN Cepoko 3. The research method used was descriptive qualitative. Data were collected through interview, observation, and documentation data collection techniques. The results showed that the implementation of guidance and counseling services at SDN Cepoko 3 was carried out by classroom teachers as counselors. The stages carried out in the implementation of guidance and counseling to students are: problem identification stage, diagnosis, setting prognosis, providing assistance, evaluation or follow-up. Services are provided in written and verbal form. The types of guidance and counseling services provided at SDN Cepoko 3 include individual guidance services and group guidance services.